Characterization of Liquid Smoke and Charcoal from Cocoa Pod Husks (Theobroma cacao L.) in North Kolaka Regency - Mochammad Wijaya; Muhammad Nur Alam; Muhammad Wiharto (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to characterize the pyrolysis products of cocoa pod waste from North Kolaka Regency, Southeast Sulawesi Province. Pyrolysis takes place at various temperatures between 112 - 512 oC and produces liquid smoke and charcoal products. The highest liquid smoke yield was obtained at a temperature of 212 oC of 20.05%. The results of GC-MS analysis showed that liquid smoke contains many potential compounds consisting of acetic acid compounds with the highest concentration of 28.1%, Phenol, 2-methoxy- (CAS) Guaiacol with the highest concentration of 4.18%, 3-Hexine-2,5-diol (CAS) Hexine-3-diol-2,5 of 2.94%, and several aromatic and alcohol compound groups. FTIR analysis shows that the typical functional groups of cocoa pod charcoal consist of OH (hydroxyl) and C = C-H (aromatic) groups. XRD analysis shows that charcoal is dominated by an amorphous phase with a degree of crystallinity of 14%. Liquid smoke and cocoa pod charcoal have the potential to be used as raw materials in the chemical, health and manufacturing industries.